Spin-Orbital Interaction and a Quantum Semiconductor Wire in Magnetic Field - Рувінський, Марк Аунович; Рувінський, Борис Маркович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The influence of spin-orbital interaction on the energetic spectrum of electrons and the effect of one-dimensional Gaussian fluctuations of spinorbital interaction on the mobility of carriers are determined for the quantum semiconductor wire in the magnetic field directioned along the wire axis. For nondegenerate statistics in the boundary case of high magnetic field at low temperatures the electron mobility un ∝ T −1/ 2H −2 .